“CRISWEED” AS AN INNOVATIVE SEAWEED BASED HEALTHY SNACK TO PROMOTE NATIONAL FOOD DIVERSIFICATION AND SECURITY - Siregar, Fikri Al-Khair; Sumartini, Sumartini; Hutagalung, Ghina Amirah Yahri; Rahmawati, Fanny; Khairani, Hilda; Simanjuntak, Dimas Adryan (Proceedings of The Vocational Seminar on Marine & Inland Fisheries, 2026)
Seaweed (Eucheuma cottoni) is known as a nutrient rich food source, containing fiber, vitamins, minerals and antioxidant compounds beneficial for health. Based on this assessing its business potential and consumer responses. The research involved a survey of 107 respondents to map market interest, followwd by a hedonic test through trial and error of five different product formulations to determine the best taste. Product quality analysis included proximate testing, texture analysis and hedonic evaluation. In addition, the business aspect was assessed through SWOT analysis, cost calculation, profit loss estimation, break even point (BEP) and R/C ratio. The results showed that Crisweed received positive acceptance as a natural and healthier snack alternative. Among the five formulations, Formula 3 received the highest hedonic score (8.27±0.18). Financially, the business was deemed feasible with an R/C Ratio of 1.15, an estimated annual net profit of approximately Rp. 12,011,543, and a BEP of 5,320 unit per year. SWOT analysis placed the bussines in Quadrant II, indicating the need for a diversification strategy to strengthen its position and expand market reach. Overall, Crisweed shows strong potential to be developed as an innovative and commercially valuable healthy snack.